2020
DOI: 10.3390/d12030110
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Metabarcoding of Eukaryotes and Prokaryotes to Elucidate the Community Structures within Tardigrade Microhabitats

Abstract: Tardigrades are microscopic invertebrates that can withstand complete desiccation, but their interspecies interactions with prokaryotes and eukaryotes within their microhabitat remain relatively unexplored. Here, I utilized combined metabarcoding of eukaryotes and prokaryotes to simultaneously identify entire community structures within xeric and mesic mosses that harbor tardigrades. The populations of organisms within the microecosystems were successfully determined in 45 xeric moss samples and 47 mesic moss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Few labs, researchers, students or citizen scientists have the resources to even try. The future may be in metabarcoding where a single environmental sample can identify the DNA of all species in the sample (Arakawa 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Few labs, researchers, students or citizen scientists have the resources to even try. The future may be in metabarcoding where a single environmental sample can identify the DNA of all species in the sample (Arakawa 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The small size of these habitats makes them amenable to experimental manipulation, or even in situ creation of new pools (see for example Evans et al, 2016;Sommers et al, 2019). In addition, their relative simplicity makes the application of metabarcoding (Arakawa, 2020;Topstad et al, 2021) possible, which would provide a complete and unbiased inventory of the meiofauna hosted in this unique and understudied ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The use of DNA metabarcoding techniques facilitate rapid, large-scale identification of species based on the presence of their DNA (Deiner et al 2017), and have the potential to circumvent the aforementioned impediments for species level identification of tardigrades in environmental samples. Recent studies have shown the advantages of metabarcoding in documenting invertebrate diversity in soils (e.g., Boggs et al 2019;Watts et al 2019), and DNA metabarcoding has been used to investigate prokaryotic and eukaryotic (including tardigrade) community structure in moss samples (Arakawa 2020). However, whether such an approach is applicable and comparable to morphological identification of tardigrades has not been investigated.…”
Section: Introductionmentioning
confidence: 99%